Kontribusi Layanan Bimbingan Kelompok dengan Teknik Talking Chips untuk Meningkatkan Kecerdasan Emosional pada Siswa Sekolah Menengah Pertama - Rona Ardelia Fauziati; Heri Saptadi Ismanto; Agus Setiawan (Scidacplus, 2026)
Emotional intelligence is a crucial developmental capacity for junior high school students, as it supports self-awareness, emotional regulation, empathy, motivation, and positive peer relationships. This study aimed to investigate the contribution of group guidance employing the talking chips technique to the enhancement of students’ emotional intelligence. A quantitative quasi-experimental method with a pretest-posttest control group design was employed. The participants were 32 eighth-grade students of SMP Negeri 3 Comal, consisting of 15 students in the experimental group and 17 students in the control group. Data were collected through observation, interviews, documentation, and an emotional intelligence questionnaire developed based on five indicators: recognizing one’s own emotions, managing emotions, motivating oneself, recognizing others’ emotions, and building relationships. The experimental group received five sessions of group guidance using the talking chips technique, while the control group did not receive the same treatment. Data were analyzed using normality testing, paired sample t-test, gain score, and normalized gain (N-gain). The results showed that the mean score of the experimental group increased from 97.53 to 104.73, while the control group increased from 98.63 to 103.71. The experimental group obtained a higher normalized gain percentage (35.67%) than the control group (25.11%). Paired sample t-test indicated a significant improvement within the experimental group (p = .001). However, the independent sample t-test on N-gain scores showed no statistically significant difference between groups (p = .228). The calculated effect size was small (Cohen’s d = 0.44). These findings indicate that group guidance using the talking chips technique contributed positively to the development of students’ emotional intelligence, although the magnitude of improvement remained limited.